Alkalihalobacterium elongatum gen. nov. sp. nov.: An Antibiotic-Producing Bacterium Isolated From Lonar Lake and Reclassification of the Genus Alkalihalobacillus Into Seven Novel Genera - Joshi, Amaraja; Thite, Sonia; Karodi, Prachi; Joseph, Neetha; Lodha, Tushar (Frontiers in Microbiology, 2021)
A Gram-stain positive, long, rod-shaped, motile and spore-forming bacterium (MEB199T) was isolated from a sediment sample collected from Lonar lake, India. The strain was oxidase- and catalase-positive. The strain grew optimally at pH 10, NaCl concentration of 3.5 % at 37 C. The major fatty acid was iso-C15:0, iso-C16:0, anteiso-C15:0, and iso-C17:0. The peptidoglycan contained meso-diaminopimelic acid. Phosphatidylethanolamine, diphosphatydilglycerol and phosphatidylglycerol, were the major polar lipids of MEB199T. Phylogenetic analysis based on 16S rRNA gene sequence showed that strain MEB199T belonged to the family Bacillaceae and exhibited a distinctive position among the members of the genus Alkalihalobacillus. Strain MEB199T shared the highest 16S rRNA gene sequence similarity with Alkalihalobacillus alkalinitrilicus ANL-iso4T (98.36 %), whereas with type species A. alcalophilus DSM 485T it is 94.91 %, indicating that strain MEB199T distinctly related to the genus Alkalihalobacillus. The G+C content of genomic DNA was 36.47 mol %. The dDDH (23.6 %) and average nucleotide identity (81 %) values between strain MEB199T and Alkalihalobacillus alkalinitrilicus ANL-iso4T confirmed the novelty of this new species. The different phylogenetic analysis based on the genome showed that the members of the genus Alkalihalobacillus separated into seven distinct clades. The intra-clade average amino acid identity and percentage of conserved proteins range from 52-68 % and 37-59 %, respectively which are interspersed on the intra-genera cut-off values, therefore we reassess the taxonomy of genus Alkalihalobacillus. The phenotypic analysis also allows corroborated the differentiation between these clades. Based on the phylogenetic analysis, genomic indices and phenotypic traits we propose the reclassification of the genus Alkalihalobacillus into seven new genera for which the names Alkalihalobacterium gen. nov., Halalkalibacterium gen. nov., Halalkalibacter gen. nov., Shouchella gen. nov., Pseudalkalibacillus gen. nov., Alkalicoccobacillus gen. nov., Alkalihalophilus gen. nov. are proposed and provide an emended description of Alkalihalobacillus sensu stricto. Also, we propose the reclassification of Alkalihalobacillus okuhidensis as a sub-species of Alkalihalobacillus halodurans. Based on the polyphasic taxonomic analysis, strain MEB199T represent a novel species of newly proposed genus for which the name Alkalihalobacterium elongatum gen. nov. sp. nov. is proposed. The type strain is MEB199T (=MCC 2982T, =JCM 33704T, =NBRC 114256T, =CGMCC 1.17254T).